OA01.03. Antisecretory and antiulcer activities of eclipta alba Linn.in rats - Samaiya, Puneet Kumar (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Eclipta alba Linn. (Asteraceae) is used traditionally in Indian system of medicine as anti inflammatory, hepatoprotective, hypoglycemic, immunomodulator, in wound healing, and as a potent hair growth promoter. The study was aimed to evaluate the antisecretory and gastroprotective effects of 50% ethanol extract of Eclipta alba. METHOD: Eclipta alba extract (EAE) at 50, 100 and 200 mg/kg was administered orally, twice daily for 5 days to prevent from, cold restraint stress (CRS), and pylorus ligation (PL) induced ulcers. Antioxidant studies were performed in CRS induced ulcer model. Gastric wall mucus and secretion parameters like volume of gastric juice, acid output and pH were estimated in PL induced ulcer model. Ranitidine (50mg/kg, p.o.) was used as positive control for comparison. RESULT: A dose dependent and significant (p < 0.05) reduction in lesion index was observed in ulcer-induced rats treated with EAE at various doses when compared with control group in both the models. Gastric wall mucus production was significantly (p < 0.05) elevated in EAE treated rats. Significant attenuation in lipid peroxidation, superoxide dismutase activity was observed, whereas, catalase enzyme levels were elevated in EAE treated groups. Antisecretory activity of EAE was evidenced by significant reduction in gastric volume, acid output and increase in gastric pH when compared to their control values. The findings were further supported by histopathological examination of stomach in both EAE treated and control rats. CONCLUSION: The results of the present investigation suggest that ethanol extract of Eclipta alba possesses potent antisecretory and gastroprotective activity. The exact mechanism to be evaluated further but in preliminary observation it was thought to be mediated through free radical scavenging activity.